2011
DOI: 10.1007/s00296-011-2233-z
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral osteomyelitis: eight years’ experience of 100 cases

Abstract: To evaluate the etiology and characteristics of vertebral osteomyelitis cases in our country, patients with vertebral osteomyelitis between January 2000 and December 2007 were included in this study. Clinical and laboratory data of the patients were collected from the medical records retrospectively. Of these 100 patients, 44 had pyogenic, 24 had brucellar, and 32 had tuberculous spondylodiscitis. The age of the patients ranged from 13 to 82 years, with a mean of (SD±) 55 ± 15.6 years. Within the pyogenic grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
39
2
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 30 publications
13
39
2
11
Order By: Relevance
“…This disease is most commonly seen in patients older than 50 years, with a male predominance and leads to significant morbidity [6][7][8][9]. The etiologic agents of VOM may be bacteria, fungi or parasites, their incidence varies in different geographical areas and with underlying diseases [7,10]. When the infecting agent is Mycobacterium tuberculosis complex, it is called ST/PD [1].…”
Section: Introductionmentioning
confidence: 99%
“…This disease is most commonly seen in patients older than 50 years, with a male predominance and leads to significant morbidity [6][7][8][9]. The etiologic agents of VOM may be bacteria, fungi or parasites, their incidence varies in different geographical areas and with underlying diseases [7,10]. When the infecting agent is Mycobacterium tuberculosis complex, it is called ST/PD [1].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that lumbar involvement was the most frequent site (69.5%) for spondylodiscitis, and one-quarter of spondylodiscitis cases involved the L3-L4 segment. In previous studies, lumbar involvement was reported as 60-78% in patients with brucellar spondylodiscitis [20,29,30]. One of these studies, the most common site was the L4-L5 segment; the level was not specified in the two other studies.…”
Section: Discussionmentioning
confidence: 97%
“…Brucella spondylitis confused with the differential diagnosis of tuberculosis spondylitis, pyogenic spondylitis, metastases, intervertebral disc herniation and spondylosis (11). Even if pyogenic causes are the most common cause of spondylodiscitis, in the endemic regions brucellosis can be the most common cause (11,12). In the story of our patient living in an endemic area for brucellosis and the story of fresh milk consumption suggested the possibility of brucellosis strongly.…”
Section: Discussionmentioning
confidence: 97%
“…The spondylodiscitis or vertebral osteomyelitis is inflammation of the intervertebral disc and the adjacent vertebral bodies. Brucella spondylitis confused with the differential diagnosis of tuberculosis spondylitis, pyogenic spondylitis, metastases, intervertebral disc herniation and spondylosis (11). Even if pyogenic causes are the most common cause of spondylodiscitis, in the endemic regions brucellosis can be the most common cause (11,12).…”
Section: Discussionmentioning
confidence: 99%